Summary Proceedings of the Fifty-First Annual Meetings of the Board of Governors, 1996. - International Monetary Fund. Secretary's Department (Washington, D.C. : International Monetary Fund, 1996)
This annual publication is a record of the IMF's Annual Meeting and contains the opening and closing addresses of the Chairman of the Board of Governors, presentation of the Annual Report by the Managing Director, statements of Governors, committee reports, resolutions, and a list of delegates. Usually published in March.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Labor Economics; Monetary Policy